2020
DOI: 10.21273/hortsci14941-20
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange and Mineral Nutrition of 12 Viburnum Taxa Irrigated with Saline Water

Abstract: More than half of residential water in Utah is used for landscape irrigation. Reclaimed water has been used to irrigate urban landscapes to conserve municipal water. High salt levels in reclaimed water may pose osmotic stress and ion toxicity to salt-sensitive plants. Viburnums are commonly used landscape plants, but salinity tolerance of species and cultivars is unclear. The objective of this study was to characterize gas exchanges and mineral nutrition responses of 12 viburnum taxa subjected to salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…However, an increasing trend was visible in both treated plants (CaCl 2 _T and NaCl_T). Finally, in several species of Viburnum, Chen et al [42] found that the leaf Cl − concentration increases with increased electrical conductivity of saline solution containing NaCl and CaCl 2 (1.5:1) and that leaf chloride concentration correlates negatively with visual score, plant height, and leaf P n and g s , but not with the leaf area.…”
Section: The Effect Of Salinity Treatment On Morpho-anatomical Traitsmentioning
confidence: 98%
“…However, an increasing trend was visible in both treated plants (CaCl 2 _T and NaCl_T). Finally, in several species of Viburnum, Chen et al [42] found that the leaf Cl − concentration increases with increased electrical conductivity of saline solution containing NaCl and CaCl 2 (1.5:1) and that leaf chloride concentration correlates negatively with visual score, plant height, and leaf P n and g s , but not with the leaf area.…”
Section: The Effect Of Salinity Treatment On Morpho-anatomical Traitsmentioning
confidence: 98%
“…These findings underscore the influence of saline solution irrigation on g s over varying timeframes. Previous studies by Chen et al (2020) and Sun (2022, 2023) reported a decrease in g s in response to higher EC levels in several ornamental plants. Elevated salinity induces osmotic challenges, leading to a protective reduction in g s to minimize water loss.…”
Section: Resultsmentioning
confidence: 79%